Multiple-scattering phase distortion in the ionization of molecules - Altszyler, E. (2012)
We theoretically analyze the multiple-scattering effects that might occur in the ionization of a molecule by the impact of photons or massive particles, by calculating the series to all orders within a muffin-tin description. We find a large sensitivity on the final state and a sizable momentum-dependent distortion of the phase-shift and frequency of the interference oscillations, that are not replicated by non-scattering or single-scattering approximations. Furthermore, our results do not validate the existence of any discernible harmonic oscillations. © Published under licence by IOP Publishing Ltd.